Non-destructive Tests on Concrete - Nepomuceno, Miguel (2018)
Concrete compressive strength of standard samples curing under standard conditions are of outmost importance for quality control of concrete as it is produced. However, those values can only be accepted as indicating the “potential strength” of concrete and may differ from the actual in-situ concrete compressive strength. The knowledge, as close as possible, of the in-situ concrete compressive strength is, in some situations, necessary in order to estimate, for instance: the time when precast concrete members can be moved and transported, the time of prestress, removal of moulds or propping, etc. Non-destructive tests (NDT) have been increasingly used in the last decades for this purpose, i. e., the assessment of in-situ quality and integrity of concrete elements, especially for estimation of the in-situ concrete compressive strength. The use of NDT methods on normal and high strength concrete elements will be evaluated on this paper qualitatively, taking as reference five different test methods, which imply the measurement of other five different properties. Such properties include the measurement of the surface hardness, ultra-sonic pulse velocity, penetration resistance, pull-out force and direct tensile strength (pull-off test).